Human Insulin Therapy Is Associated With an Increased Risk of Lung Cancer: A Population-Based Retrospective Cohort Study - Tseng, Chin-Hsiao (Frontiers in Endocrinology, 2019)
Background: Whether human insulin may affect lung cancer risk requires investigation. Methods: All patients with a diagnosis of diabetes mellitus from 1996 to 2009 were enrolled from Taiwan’s National Health Insurance. An entry date was set on January 1, 2004 and 1,007,617 patients with type 2 diabetes mellitus diagnosed before 2004 were followed up for new-onset lung cancer until December 31, 2009. Incidence rates of lung cancer for never-users, ever-users and tertiles of three dose-response exposure parameters (i.e., time since starting insulin, cumulative dose and cumulative duration) were calculated. Adjusted hazard ratios were estimated by Cox proportional hazards models. The joint effect of insulin and chronic obstructive pulmonary disease was also evaluated. Results: There were 156,720 ever-users and 850,897 never-users. The respective case numbers of incident lung cancer were 3007 (1.92%) and 13,677 (1.61%), and the respective incidence rates were 424.45 and 313.60 per 100,000 person-years. The adjusted hazard ratio comparing ever-users versus never-users was 1.545 (95% confidence interval: 1.478-1.614). The hazard ratios for the different subgroups of the three dose-response parameters all suggested a significantly higher risk of lung cancer associated with insulin use (P-trend <0.0001). While compared to patients without insulin use and without chronic obstructive pulmonary disease, insulin users who also had chronic obstructive pulmonary disease had the highest risk of lung cancer (adjusted hazard ratio: 1.891, 95% confidence interval: 1.767-2.024). Conclusions: This study suggests a significant association between human insulin use and lung cancer risk in patients with type 2 diabetes mellitus.